2022
DOI: 10.7189/jogh.12.05015
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic increases in knowledge, attitudes and practices of COVID-19 observed among low-income households in the Philippines: A repeated cross-sectional study in 2020

Abstract: Background The COVID-19 pandemic has severely impacted populations globally, and knowledge, attitudes and practices (KAPs) surrounding the virus have necessarily evolved. This study was conducted in partnership with International Care Ministries (ICM), a Philippine-based non-governmental organization that runs the “Transform” poverty alleviation program. The main objective of this study was to describe the changes in COVID-19 KAPs among households experiencing extreme poverty in the Philippines ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Both surveys showed the lowest ratings related to illness coherence, reflecting the ability to make sense of and cope with the pandemic. These findings suggest that mental representation of COVID-19 changed in some ways, and what is common to our results and those reported by others is the increase in knowledge about COVID-19, stronger sense of negative emotions and consequences of COVID-19 after several waves of the pandemic [4,31,[33][34][35][36]39]. Our findings are consistent with results reported in a longitudinal study [24], which showed that the highest level in the hierarchy of COVID-19 representations was occupied by a sense of negative consequences, while the lowest level was occupied by sense of personal control.…”
Section: Discussionsupporting
confidence: 90%
“…Both surveys showed the lowest ratings related to illness coherence, reflecting the ability to make sense of and cope with the pandemic. These findings suggest that mental representation of COVID-19 changed in some ways, and what is common to our results and those reported by others is the increase in knowledge about COVID-19, stronger sense of negative emotions and consequences of COVID-19 after several waves of the pandemic [4,31,[33][34][35][36]39]. Our findings are consistent with results reported in a longitudinal study [24], which showed that the highest level in the hierarchy of COVID-19 representations was occupied by a sense of negative consequences, while the lowest level was occupied by sense of personal control.…”
Section: Discussionsupporting
confidence: 90%
“…Various studies have evaluated KAP related to COVID‐19 among pregnant women, 15,18–22 but none have assessed the trends over time in pregnant women's KAP across sites. However, a few single‐ and multi‐site studies have examined the changes over time in KAP related to COVID‐19 in the general population 23–26 . In this large multi‐site study, we had an opportunity to examine trends in COVID‐19 KAP among pregnant women of seven LMICs over a period of 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, a few singleand multi-site studies have examined the changes over time in KAP related to COVID-19 in the general population. [23][24][25][26] In this multi-site study, we had an opportunity to examine trends in COVID-19 KAP among pregnant women of seven LMICs over a period of 2 years.…”
Section: Interpretationsmentioning
confidence: 99%
“…Because of the lack of vaccines and limited antiviral therapies during the early phase of the COVID-19 pandemic, NPIs such as wearing of masks, school and workplace closures, and travel restrictions were crucial disease control measures. In the Philippines, compliance to policies was not only prompted by public heath campaigns, but also driven by uncertainty and anxiety about the disease, and fear of getting reprimanded by the authorities [13, 14, 15]. Some of those who got infected suffered stigma and were blamed for not following the protocols [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Some of those who got infected suffered stigma and were blamed for not following the protocols [16, 17]. A study among low income households in the Philippines done in the early phase of the pandemic reported that 66% of respondents who might experience symptoms considered staying at home instead of seeking medical attention [13].…”
Section: Introductionmentioning
confidence: 99%